Facilitating mobile access to social media content on urban underground metro systems - Wu, Di; Lambrinos, Lambros; Przepiorka, Thomas; McCann, Julie A. (My University, 2016)
Users of mobile devices require ubiquitous Internet connectivity especially when located in urban areas. However, when using a city's underground metro system there are often situations where there is no signal coverage for a considerable time period. One large city facing this issue is London whose underground metro system includes a significant number of lines using deep level tunnels. To facilitate mobile Internet connectivity for travellers using these lines we designed DeepOpp, a context-aware system that enables offline access to social media content. This access is achieved by prefetching and caching content when connectivity opportunities (such as urban 3G or station WiFi) arise. DeepOpp can measure signal characteristics (strength, bandwidth and latency) and based on current and historical information make signal coverage predictions in order to activate data prefetching of social media content. An Android-based implementation of DeepOpp has enabled us to carry out real tests on the London underground and demonstrate its benefits which promote it as a viable solution for cities with similar metro systems such as New York, Paris and Shanghai.
Keywords: Mobile communication; Media; Prefetching; Mobile computing; Mobile handsets; Internet; Urban areas